Assessment of Readiness for Implementation of Tourism Related Internship for Students in the Del Institute of Technology - Niko Saripson Pandapotan Simamora; Roy Deddy Hasiholan Lumban Tobing; Cynthia Nababan; Vinny Sihombing; Fadly Riscky Sirait; Aldy Oki Jatnika Putra; Anggi Retta Natalia Panjaitan; Chindi May Pasaribu (Institute of Computer Science (IOCS), 2022)
The Independent Learning Campus Program (MKBKM) launched by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia is one of the breakthroughs in the era of digitalization in the education sector. This program enables student exchange and also opens the boundaries of the (physical) classroom into a digital space. This study aims to analyze the implementation of the MBKM program at the Del Institute of Technology in the implementation of tourism-related internships. In addition, this study also aims to identify the needs of tourism business actors (operators) related to assistance and support from universities with the MBKM scheme in Toba Regency, North Tapanuli Regency, and Samosir Regency, as well as providing an overview of student interests and roadmaps for research and community service for lecturers and study programs within the IT Del environment to improve higher education achievements related to Key Performance Indicators (KPI). This activity combines qualitative and quantitative research. The technique used is by conducting surveys and focus group discussions (FGD). The results of this activity indicate that the MBKM program is generally known by the academic community and tourism business actors (operators), universities and operators are willing to establish partnerships in the MBKM program, and it is necessary to increase the role of universities and tourism business actors in supporting tourism development through the MBKM program.